Нові знахідки бріофільних дискоміцетів з Харківського Лісостепу - Морозова, І.І. (Харківський національний університет ім. В.Н. Каразіна, 2014)
Records of 3 bryophilous species of operculate Discomycetes are reported. Among them Neottiella atrichi Benkert is a new record for Ukraine, N. vivida is firstly reported for the Left-Bank Ukraine. Identification of Discinella aff. Schimperi (Navashin) Redhead et K. W. Spicer requires additional effort.
New finds of bryophillous discomycetes from Kharkiv Forest-Steppe
Keywords: bryophyllous; discomycetes; Neottiella vivida; Neottiella atrichi; Discinella schimperi; Ukraine